Defense management reform : how to make the Pentagon work better and cost less - Levine, Peter, 1957- (Stanford University Press, 2020)
"This book addresses why, despite decades of attempted reform, the Pentagon continues to struggle to reduce waste and inefficiency. Peter Levine narrates the history of attempted reforms through three case studies in civilian personnel, acquisition, and financial management in the Department of Defense. The result is a clear understanding of what went wrong in the past and a set of concrete guidelines to plot a better future."--